The first experience of using of {99}mTc-Al[2]O[3] for detection of sentinel lymph nodes in breast cancer; IOP Conference Series: Materials Science and Engineering; Vol. 135 : Issues of Physics and Technology in Science, Industry and Medicine - Doroshenko A.; Chernov V. I. Vladimir Ivanovich; Medvedeva А. А. Anna Aleksndrovna; Zelchan R. V. Roman Vladimirovich; Slonimskaya E.; Varlamova N. V. Natalya Valeryevna; Skuridin V. S. Viktor Sergeyevich; Dergilev A.; Sinilkin I. G. Ivan Gennadjevich (2016, 2016)
Title screen